Priporočila za zelene prireditve: Primer prireditve Praznik kozjanskega jabolka (University of Maribor Press, 2021)
Recommendations for Green Events: an Example of the Kozjansko Apple Festival. One of the key attractive elements of the tourist offer are events. We know several types of events, such as cultural, sports, educational. Essential elements of events are certainly their content, as well as the gastronomic offer. Collective brands are an important tool for rural development and chain-linked providers, providing comprehensive, high-quality gastronomic and related offerings from pitchfork to forks and guided experiences and green events with local added value. The organization must ensure the best possible quality of performance and ensure the safety and sustainable orientation of the event, as discussed in this monograph. The guidelines for a sustainable green event might guide the future development of events in Podčetrtek, Bistrica ob Sotli and Kozje, where they joined a sustainable future tourism solutions project in cooperation with the Faculty of Tourism of the University of Maribor. We studied green events on the example of the Kozjansko Apple Festival.